The incomparable salesmen : - Stryker, Perrin (McGraw-Hill, 1967)
This book makes no attempt to disguise or submerge the stereo typed image of the life insurance agent. That image is founded in relity, and can be seen today in hundreds of thousands of those uninspiring products of the industry's hiring, training, and marketing practices.